Exploring the Maxims of Filipino Kanal (canal) Humour through Semantic Analysis - Abegail Baring; Betty Mae Albia; Angelie Guevarra; John Jonathan N Normandia; Ruel Bonganciso (RSF Press, 2025)
This study aims to systematically and semantically analyze kanal humour in conversation– its feature, the meaning behind it, as well as what it conveys or expresses to give clarifications and a more profound understanding of kanal humour. This study used the Semantic Analysis method to analyze and interpret the content of Kanal humour in Tiktok videos. Furthermore, the result shows that kanal humour uses specific linguistic strategies, such as homophonic puns and double entendres, and violates maxims of conversations to subvert expectations and entertain. The analysis of